2008
DOI: 10.1063/1.2896653
|View full text |Cite
|
Sign up to set email alerts
|

The shock-densification behavior of three distinct Ni+Al powder mixtures

Abstract: The shock-densification response of equivolumetric mixtures of Ni+ Al powders of varying particle size and morphology has been determined through instrumented parallel-plate impact experiments. The results reveal a variation in the densification response, with crush strengths ͑stress at full density͒ ranging from 0.5 to nearly 6 GPa. A modified Fischmeister-Artz contact model was proposed to predict the crush strength of configurationally varying Ni+ Al powder mixtures. © 2008 American Institute of Physics. ͓D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…The most studied of these reactive materials are Al-based composite such as Al/Ni and Al/W owing to their high strength, high energy density, easy processing characteristics and rapid energy release properties. [5][6][7][8][9][10][11][12] To improve their intercept efficiency, some high density reactive fragments have been proposed as alternatives to traditional steel fragments of anti-air warheads. For instance, tungsten/zirconium (W/Zr) composites have enough mechanical strength to maintain stability under overload during warhead detonation, and can penetrate targets and rapidly react.…”
Section: Introductionmentioning
confidence: 99%
“…The most studied of these reactive materials are Al-based composite such as Al/Ni and Al/W owing to their high strength, high energy density, easy processing characteristics and rapid energy release properties. [5][6][7][8][9][10][11][12] To improve their intercept efficiency, some high density reactive fragments have been proposed as alternatives to traditional steel fragments of anti-air warheads. For instance, tungsten/zirconium (W/Zr) composites have enough mechanical strength to maintain stability under overload during warhead detonation, and can penetrate targets and rapidly react.…”
Section: Introductionmentioning
confidence: 99%
“…The extent and distance over which these waves can be attenuated are important properties for shock mitigation, and rely upon understanding the behavior of powders under strong and weak loading. While earlier studies have shown the high stress behavior of porous materials to be insensitive to powder configuration [1], prior work on metal powder mixtures demonstrated that both powder morphology and particle size play a strong role in densification at low stresses [2,3].…”
Section: Introductionmentioning
confidence: 95%
“…For the low stress regime, the Wu-Jing model implements the Carrol-Holt form of the P − α model [5]. In the present study, the P − α model was modified according to the method outlined in [3], in which a configuration parameter, n, was introduced to take into account the surfacearea of the various powders. This parameter was used to scale the Fischmeister-Artz crush-strength, and establish new limits for the Wu-Jing crush-up regime.…”
Section: Experiments Detailmentioning
confidence: 99%
“…For dynamic behavior of Al/Ni composites, SHPB and high velocity flyer plate impact methods are used to determine the stressestrain relationship or EOS of the material. Eakins and Thadhani [20,29,30] conducted Hugoniot measurement experiments on Ni and Al powders of varying particle size and morphology mixed at a 1:1 volumetric ratio. In the experiments, "polyvinylidene fluoride (PVDF)" gauges coupled with "Velocity Interferometer System for Any Reflector (VISAR)" data were used to determine the shock states.…”
Section: Introductionmentioning
confidence: 99%